Cult of the Virgin Sisters - Arroyo Aguilar, Sabino (2013)
The “Virgen de las Nieves” cult from Qasiri and Coracora village show us two kind of models of family and goverment organization: 1. The unstructured family with high predominance of the women decisions, this model is desappearing. 2. And the improvement of the familiar union as the basis of the goverment organization, this model is getting more prevalent.